The Relationship Between Supplementary Feeding Consumption Made from Local Foods and the Nutritional Status of Wasting and Stunting Toddlers - Rachmah, Siti; Mawaddah, Nurul; Rahim, Rhisma Andini Ainul (Al-Hijrah Indonesia, 2025)
Indonesia still faces nutritional problems in toddlers, especially malnutrition (wasting) and stunting, which can lead to the loss of a quality generation. The government has implemented a PMT (Supplementary Feeding) program made from local foods to improve nutritional problems in toddlers. The purpose of this study was to examine the relationship between the consumption of PMT made from local foods and the nutritional status of toddlers with wasting and stunting. This study used a quantitative method with an analytical observational research type that used an ex post facto research design. Sampling used a proportional random sampling technique with a total of 43 respondents. Data collection techniques used an interview guide sheet, an observation sheet for changes in nutritional status in the form of weight data before and after the PMT program was implemented. The results of the study after conducting interviews with toddler mothers showed that the majority of respondents (58.1%) had consumed PMT made from local foods in accordance with the program's recommendations, and as many as 58.2% of respondents experienced an increase in nutritional status after being given PMT made from local foods according to the program. The results of statistical tests showed a significant relationship between the consumption of PMT made from local foods and the nutritional status of toddlers. Consumption of PMT made from local foods can improve the nutritional status of toddlers with malnutrition and stunting.